The effect of spiritual intelligence on organisational entrepreneurship: case study of educational departments in University of Tehran. (16th May 2019) - Tajpour, Mehdi; Salamzadeh, Aidin
The aim of this study is to investigate the effect of spiritual intelligence on organisational entrepreneurship. The present research has a practical approach, and in terms of data collection is a descriptive-survey which follows a quantitative approach. The statistical population of the study consisted of the employees of the educational departments of University of Tehran. By using a random sampling method and Cochran's formula, 140 subjects were considered as the sample size. Data analysis is performed using structural equation modelling (SEM) and Smart PLS software. The results of the research showed that spiritual intelligence had an 84% effect on organisational entrepreneurship. Also, the results of sub-assumptions showed that critical thinking (77%), personal presentation (13%), transcendental consciousness (37%), and establishing a position of consciousness (41%) affect organisational entrepreneurship.